Leisure Regulations versus Domestic Tourism in the People’s Republic of China: a Case Study of Macau and Yunnan Province - Rettinger, Renata; Łyczkowski, Hubert (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2025)
In countries with high levels of tourism and demographic potential, such as the People’s Republic of China (PRC) domestic tourism is developing dynamically. In recent years, China has seen steady growth in domestic tourism throughout the country supported by factors such as its attractive natural and cultural landscapes, the increasing formal restrictions on travel throughout the country, and the development of tourism infrastructure. Domestic tourism in China encounters numerous barriers that significantly slow its development. These conditions manifest themselves in various dimensions: social, economic and environmental. One of the most important issues is that of free time, particularly state regulations regarding its quantity and timings. The limited amount of vacation time for the average employee necessitates travel during public holidays, which leads to a significant temporal and spatial concentration of tourism in a country with enormous demographic potential. The PRC government’s tourism policy is characterized by a high degree of interventionism, relying on prescriptive instruments to guide the operation and development of the country’s tourism economy, addressing both demand and supply. This study utilizes case studies of two different regions: the Macau Special Administrative Region and Yunnan Province. Its aim is to analyze the volume and distribution of leisure time as a key factor influencing the development of domestic tourism, particularly in the context of selected tourist regions. The methods employed include literature studies and comparative analysis.